Regional Chitosan and Melaleuca armillaris Essential Oil with Mesoporous Glass Particles for Enhancing Bioactive and Antibacterial Behaviour of Ti6Al4V Implants - Buldain, Daniel; Diaz, Florencia; Ünalan, Irem; Mestorino, Nora; Boccaccini, Aldo R.; Ballarre, Josefina (Arabian Journal for Science and Engineering, 2025)
Metal implants have long been studied and used for applications related to bone tissue engineering, thanks to their outstanding mechanical properties and appropriate biocompatibility. However, due to their lack of bioactivity, many implants struggle with osteointegration and attachment, and can be vulnerable to the development of infections. In this work, we have developed a composite coating via electrophoretic deposition which is both bioactive and antibacterial. We have loaded a combination of Melaleuca armillaris essential oil and gentamicin into mesoporous bioactive glass particles, and incorporated the nanoparticles into a chitosan solution electrophoretically deposited onto the titanium substrate. This coating significantly improves the antibacterial activity against both gram-positive and negative strains of bacteria compared to the bare substrate. The coating is biocompatible, as MG63 cells seeded on the coated materials exhibit their typical spindle-like morphology and can grow into a smooth layer on the surface after 7 days.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Antibacterial effect; Bone regeneration; Chitosan; Electrophoretic deposition; Essential oils; Gentamicin; Mesoporous bioactive particles